Corporate social responsibility management in Uganda Lessons, challenges, and policy implications - Katamba, David; Tushabomwe Kazooba, Charles; Babiiha Mpisi, Sulayman; Nkiko, Cedric M.; Nabatanzi-Muyimba, Annet K.; Kekaramu, Jean H. (International Journal of Social Economics., 2012)
The purpose of this study is to investigate how business enterprises in Uganda manage their corporate social responsibility (CSR) activities and projects. Design/methodology/approach – The investigations focused on a limited number of management facets. Using a cross-sectional survey design, the researchers collected data through both qualitative and quantitative methodologies. These included semi-structured interviews with managers of selected enterprises, as well as non-participant observation of CSR activities and projects. Findings – The findings show unbalanced engagement in CSR for business managers in Uganda. Managers are largely motivated towards CSR by external factors such as attracting and retaining customers, enhancing reputation and operational efficiencies to achieve competitive advantage, rather than internal factors such as CSR policies, employee welfare and CSR reporting. Another significant finding is that the responsibility to initiate, administer, and monitor CSR activities is largely vested in middle-level managers. These factors pose many challenges to CSR implementation amongst managers in Uganda. Originality/value – This study was a follow-up of a baseline survey, “CSR in Uganda: perceptions, approaches, and needs of companies”, which was conducted earlier by the lead researcher. The value of this paper is that it provides an in-depth insight into the status of CSR management in Uganda, which in turn will help both the public and private sectors to identify potential gaps, weaknesses and/or needs for improvement. In the long run, this will improve the image, development impact and performance of CSR undertakings for the benefit of all stakeholders in Uganda
Keywords: Management; Corporate social responsibility; Motivation; Communication